Effects of Burdock Extract Preparation on Gastric Mucosal Protection - CHEN, FU-AN; LEE, SHIH-CHIANG; CHAO, HOW-RAN; FU, WEN-CHENG; HSU, MEI-CHICH; HORNG, CHI-TING; WANG, CHING-CHIUNG; MATSUI, HIROFUMI; AGORAMOORTHY, GOVINDASAMY (Asian Journal of Chemistry, 2010)
The root of burdock (Arctium lappa L.) has long been cultivated as a popular vegetable in Taiwan and Japan for dietary use and folk medicine. The present study investigates the effects of Bao-Jian burdock extract powders (BJBEP), a commercialized burdock extract preparation, on gastric mucosal protection. In vitro study, BJBEP revealed significant protection on rat gastric mucosal cells, RGM1, from indomethacin (INDO)-caused cytotoxicity at the concentration of 125-1000 ppm, whose efficacy was comparable with that of sucralfate from a concentration point of view. In vivo study, ethanol-induced acute gastric mucosal lesions (AGML) were applied to assess the gastroprotective activity of BJBEP in rats. BJBEP was able to decrease significantly the AGML areas caused by ethanol at the dose of 260 to 2600 mg/kg/bw. Total polyphenols in BJBEP was in proportion to its free radical scavenging activity which could be involved in biological function of gastric mucosa protective activity. The overall results indicate that BJBEP has protective effect on INDO-induced gastric mucosal cytotoxicity in vitro and ethanol-induced AGML in rats.